The Internalities & Externalities on the MSMEs in Indonesia as a Commitment on Organizational Development - Timotius Agus Rachmat; Irma M Nawangwulan; DC Ethan Samuel; Abdul Haris Lahuddin; Daniella CE Samuel; Anantadjaya, Samuel PD; Mohammad Wahiddudin; Sasotya Pratama (Salus Publica: Journal of Community Service, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia are vital to economic development but face challenges from internal and external factors. This study investigates how (1) internalities, such as; leadership and innovation capacity, and (2) externalities, such as; government policies and market competition, influence MSMEs’ commitment to organizational development. Data were gathered from 16 MSMEs in Sulawesi Barat, Sulawesi Selatan, Sulawesi Tenggara, and Eastern Java through surveys and interviews. Results indicate that strong internal and external factors (entrepreneurial orientation, dynamic capabilities, operational efficiency, market orientation, digital transformation, policy support, market environment, and collaborative network). This training really encouraged a collaborative learning process and strengthening networks between MSMEs. This activity showed that a practice-based training approach to ensure the best internalities and externalities of organizational commitment. However, access to technology and capital remains a critical barrier. The study highlights the need for targeted policy interventions and capacity-building programs to align internal strengths with external opportunities. By proposing a framework for sustainable organizational development, this research contributes to the literature on MSMEs and offers practical recommendations for stakeholders in Indonesia’s economic ecosystem